Penerapan P5 dengan Tema Hidup Cinta Lingkungan dalam Mengembangkan Karakter dan Peduli Lingkungan pada Siswa Kelas 1 SD Negeri 74 Kota Bengkulu - Cici Dwi Jayanti; Fenti Yurni; Rika Andriyani; Via Marlistina (Yayasan Darussalam Bengkulu, 2024)
Based on observations made by researchers in class 1 of SDN 74 Bengkulu City, there are still children whose environmental care character has not developed, this is because the habits carried out by the teacher there have not been implemented optimally. The data collection tools used are observation, interview and documentation methods. With data reduction analysis techniques, data presentation and conclusion drawing. Based on the results of the study, the authors can conclude that in the process of teachers in developing children's environmental care character through habituation methods there are still habituation steps that have not been carried out by teachers, namely teachers still do not remind children who forget to do positive habits in protecting the environment. Therefore, the teacher's process in developing the character of environmental care in children must be carried out through habituation methods that are carried out repeatedly.